PERAN EDUKASI DAN SOSIALISASI DALAM MENUMBUHKAN JIWA KEWIRAUSAHAN BERBASIS ISLAM TERHADAP GENERASI MILENIAL DI INDONESIA - Dwi Kurniasari; Muhammad Iqbal Fasa; Suharto Suharto (Jurnal Bina Bangsa Ekonomika, 2022)
Entrepreneurship is closely related to making the millennial generation more creative and independent. This study aims to determine how big the role of education and socialization in fostering an Islamic-based entrepreneurial spirit for the millennial generation in Indonesia. So that later the millennial generation can create jobs for themselves and others. The research was conducted in the form of a narrative method with qualitative data analysis. The results show that entrepreneurship education and socialization seeks to provide millennial generations with knowledge, skills and motivation. Entrepreneurship Education focuses on developing the understanding and capacity to pursue entrepreneurial behaviors, skills and attitudes in very different contexts. The most important entrepreneurial principle is to be brave or get out of the fear of failure